Investigating the influence of the physical environment on psychiatric nurses wellbeing and professional interactions: A convergent parallel mixed-method study protocol - Milica Vujovic; Maja Kevdzija; Friedrich Neuhauser; Matthäus Fellinger (PLoS ONE, 2026)
Nurses in psychiatric hospitals face demanding working conditions, where high emotional burdens, unpredictable patient behavior, and safety concerns contribute to stress. Research highlights the significant impact of the physical environment on healthcare workers’ experiences, with environmental factors either reducing or increasing stress levels, affecting professional interactions, and influencing job satisfaction and well-being. Despite growing recognition of these effects, there remains a need for robust, evidence-based methodologies to systematically examine how specific spatial features impact psychiatric nurses’ experiences. This study protocol aims to develop and test scalable and structured methods to evaluate the influence of the physical environment on stress levels, professional interactions, and spatial perceptions among psychiatric nurses. Conducting research in psychiatric hospitals presents unique challenges, requiring methodologies that consider the sensitive nature of the setting. Issues such as patient confidentiality, changeable work dynamics, and psychological demands on staff require a carefully tailored data collection approach. This study protocol addresses outlined concerns by selecting methods and equipment that minimize disruptions while ensuring reliable and meaningful data collection. Observations are conducted unobtrusively, and the study design prioritizes ethical considerations, ensuring participant comfort and patient privacy. The study employs a convergent parallel mixed methods design, simultaneously collecting and analyzing qualitative and quantitative data. Quantitative measures include wearable sensors tracking heart rate variability, light exposure, and physical activity alongside surveys and systematic in-person observations of professional interactions. Qualitative data, gathered through semi-structured interviews, explores nurses’ perceptions of their work environment and stress levels. The study aims to provide new insights relevant to interdisciplinary research, demonstrating the value of integrating architectural and healthcare perspectives to improve the design of therapeutic and work-friendly environments.